Surrounding Rock Stresses on a Working Face-End Roof under Mining Influence - Kang Wang; Xinglong Huang; Haibo Li; Feng Zhang; Jiazhen Li; Zhijie Zhu (Advances in Civil Engineering)
The evolution process of the surrounding rock failure mechanism is studied because of spalling and roof fall accidents at the top corner of longwall top coal caving faces affected by mining and the difficulty of moving the advanced end support. Methods are proposed to improve the stability of surrounding rocks at the top corner of the end including cutting at the top corner of the end, reinforcing the anchor cable, changing the stress distribution of surrounding rocks at the top corner of the end, and transferring the stress concentration area of surrounding rocks to the deeper rock. Field observations of the surrounding rocks at the top corner of the 15107 fully mechanized caving face show that the stress value of the surrounding rocks at the corner between the roof of the return airway and the coal wall of the working face is 28.9 MPa when the surrounding rocks are in a stable state without mining. The stress value of surrounding rocks at the top corner of the end is 32.3 MPa when it is affected by mining, which results in spalling and roof fall. The surrounding rocks are in a stable state when the maximum stress of the surrounding rocks at the top corner of the reinforced anchor cable’s back-end is 26.1 MPa. The results show that cutting of the surrounding rocks at the top corner of the end and the reinforcement of the anchor cable can avoid the spalling and roof fall when the top corner of the end is affected by mining and can ensure that the end support advances and working face moves forward.